2005
DOI: 10.1007/s00417-004-1009-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of cerebral blood flow by stimulating amblyopic and fellow eye

Abstract: The decreased activation of blood flow in the contra-lateral V1 by low temporal frequency stimuli supports the hypothesis that the parvocellular pathway in amblyopic eyes is depressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Furthermore, the results of the AMB group differ from those of the normal group most clearly in the lower temporal frequencies (pattern reversal rates 5 and 10 Hz), and in the first harmonic component. Recent functional MRI scanning and PET studies support those results [13,14].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, the results of the AMB group differ from those of the normal group most clearly in the lower temporal frequencies (pattern reversal rates 5 and 10 Hz), and in the first harmonic component. Recent functional MRI scanning and PET studies support those results [13,14].…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, decreased visual acuity caused by amblyopia should mainly affect the lower frequencies where P pathway is predominant [14]. Furthermore, amblyopia has been found to decrease the amplitude and increase the latency of the transient VEP [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown reduced cerebral blood flow and glucose metabolism in V1 and extrastriate cortex for amblyopic eye viewing. [21][22][23][24][25][26][27] Nevertheless, these studies have not yielded a consistent answer regarding the spatial extent of the effect, and the relative deficit in V1 versus V2 remains unclear. Most studies have not localized deficits to specific visual areas or field locations, with some exceptions.…”
mentioning
confidence: 90%
“…The significance of each region was estimated using distributional approximations from the theory of Gaussian fields (Worsley et al 1999). We used a direct comparison of homologous with the flipped images in the right-left direction to determine if there was any lateralization in the activity of the M1 or other areas during each task (Mizoguchi et al 2005;Callan et al 2006). We created flipped images of all the PET images and subtracted the flipped contrast images (flipped task image minus the flipped rest image) and non-flipped contrast images (non-flipped task image minus the non-flipped rest image).…”
Section: Data Processing and Statistical Analysesmentioning
confidence: 99%